The Role of Brand Image in Mediating the Relationship between Product Quality and Purchasing Decisions - Uwes Hermawan; Agus David Ramdansyah; Liza Mumtazah Damarwulan (Indonesian Journal of Innovation Multidisipliner Research, 2025)
This study was conducted to determine the effect of brand image in mediating the relationship between product quality and purchasing decisions on Wardah products in Serang City. This study used 190 samples with accidental sampling method. The data used are primary data obtained from the results of questionnaires filled out by 190 wardah product customers in the city of Serang, and secondary data obtained from wardah sales data, published books and journals. The data analysis technique used is descriptive statistical analysis, inferential statistics which include validity and reliability tests. Data processing is done using the Smart PLS 3.0 analysis tool. The results showed that product quality has a positive and significant effect on purchase decisions. Product quality has a positive and significant effect on brand image. Brand image has a positive and significant effect on purchase decision. Brand image can mediate the relationship between the effect of product quality on purchase decision.